2007
DOI: 10.1002/smll.200600536
|View full text |Cite
|
Sign up to set email alerts
|

One‐Step Production of Polymeric Microtubes by Co‐electrospinning

Abstract: Herein we demonstrate the ability to fabricate polymeric microtubes with an inner diameter of approximately 3 microm through co-electrospinning of core and shell polymeric solutions. The mechanism by which the core/shell structure is transformed into hollow fibers (microtubes) is primarily based on the evaporation of the core solution through the shell and is described here in detail. Additionally, we present the filling of these microtubes, thus demonstrating their possible use in microfluidics. We also repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
214
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(227 citation statements)
references
References 45 publications
(37 reference statements)
11
214
0
Order By: Relevance
“…To estimate the actual evaporation time, a tubular nanofiber, [54][55][56] filled with solvent, is examined. This system can be considered as an extreme case of the model discussed 47 by Guenther et al 36 Use of such tubular nanofibers enables in situ tracking of the kinetics of solvent evaporation through the nanofiber shell.…”
Section: Postprocesses Relaxation In Electrospun Nanofibersmentioning
confidence: 99%
“…To estimate the actual evaporation time, a tubular nanofiber, [54][55][56] filled with solvent, is examined. This system can be considered as an extreme case of the model discussed 47 by Guenther et al 36 Use of such tubular nanofibers enables in situ tracking of the kinetics of solvent evaporation through the nanofiber shell.…”
Section: Postprocesses Relaxation In Electrospun Nanofibersmentioning
confidence: 99%
“…[26][27][28] It has been applied in controlling secondary structures of nanofibers, encapsulating drugs or biological agents into polymeric nanofibers, fabricating polymeric microtubes, preparing nanofibers from materials that lack filamentforming properties, and enclosing functional liquids within the fiber matrix. [29][30][31][32][33] Through modifications, nanofiber diameters can be manipulated for controlling the size of self-assembled nanoparticles, preparing ultrafine structures from concentrated polymer solutions, and improving nanofiber quality systematically. [34][35][36][37][38][39] Based on the above knowledge, we report on the formation of a novel solid dispersion in the form of coresheath nanofibers produced using a coaxial electrospinning process.…”
Section: Introductionmentioning
confidence: 99%
“…8D illustrates the conditions around a bacterium cell inside a cross-linked FDMA fiber. In contrast to the fibers reported previously (13)(14)(15)(16)(17), which are composed of a water-insoluble polymer shell around a hollow core formed by dissolution of a hydrophilic component, the fibers discussed here are formed around the bacterium from a uniform hydrophilic polymer solution. When immersed in water, the crosslinks prevent the fibers from dissolving and lead to the formation of a mesh-like network of the swollen polymer within a short time (Fig.…”
Section: Resultsmentioning
confidence: 65%
“…Previous studies have reported the encapsulation of biological molecules such as enzymes, proteins, or animal cells in polymer fibers by co-electrospinning (13)(14)(15)(16)(17). In this process, 2 different solutions are spun simultaneously using a spinneret with 2 coaxial capillaries to produce core/shell fibers.…”
mentioning
confidence: 99%